Iodine release and antibacterial effects of a wound paste combined with PVP-iodine powder and/or solution in vitro - KrÃ¤mer, Mark; Sahrmann, Philipp; Sener, Beatrice; Thurnheer, Thomas; Attin, Thomas; Schmidlin, Patrick R. (International Journal of Dental Research, 2013)
Background: Improvements of the substantivity of antibacterial agents in periodontal pockets during active therapy is still a challenge. With this study, the release kinetics of PVP-iodine by simply creating mixtures of a PVP-iodine solution and powder incorporated in different concentrations into a commercially available wound paste was investigated. It was postulated that this approach could result in an extended iodine release of at least one hour resulting in adequate antibacterial concentrations. Methods: Iodine concentrations released by different formulations were determined by a titration method and the antibacterial effect was investigated using an agar diffusion method assessing the inhibition zone of two representative periopathogenic bacteria (Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis).Results: A prolonged release kinetic with up to one third of iodine released after one hour and even an ongoing release up to 4 hours was shown. The cumulative concentrations in the immersion solutions were sufficiently high to effectively inhibit bacterial growth in the agar test. The pH of the different mixtures was adequately buffered when tested in SBF as immersion medium, but resulted in acidic conditions when water was used.Conclusions: Simple mixing of PVP-powder to an available wound paste may offer an easy method to prepare antibacterial products in-office with a potential pocket disinfection duration during the scaling and root planning appointment. Nevertheless, its therapeutic usefulness under clinical conditions needs further investigation and potential side-effects require clarification.